Parasitism of Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) by Strongygaster brasiliensis (Towsend) (Diptera: Tachinidae) - Castro-Guedes, Camila Fediuk de; Dios, Rodrigo de Vilhena Perez; Almeida, Lúcia Massutti de (EntomoBrasilis, 2018)
Abstract. Harmonia axyridis (Pallas) is a Coccinellidae species originating from northeast Asia and used in biological control of aphids. As an exotic species is very important to know its natural enemies. Thus, this paper provides the first record of Strongygaster brasiliensis (Towsend)(Diptera: Tachinidae) parasitizing H. axyridis in Southern Brazil. Parasitismo de Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) por Strongygaster brasiliensis (Towsend)(Diptera: Tachinidae) Resumo. Harmonia axyridis (Pallas) é uma espécie de Coccinellidae originária do Nordeste da Ásia e utilizada como agente de controle biológico de afídeos. Como é uma espécie invasora é muito importante conhecer seus inimigos naturais. Dessa forma, este trabalho fornece o primeiro registro de Strongygaster brasiliensis (Towsend)(Diptera: Tachinidae) parasitando H. axyridis no sul do Brasil.